Emerging markets, sustainable methods: political economy empowerment in South Africa's Rooibos tea sector - Keahey, Jennifer Anne, author; Raynolds, Laura T., advisor; Murray, Douglas L., committee member; Peek, Lori, committee member; Littrell, Mary A., committee member (Colorado State University. Libraries, 2013)
Twenty-first century markets require rapid and coordinated response to emerging trends in standards and certification, yet inequitable functioning is hindering the ability of global commodity networks to achieve more effective alignment. To begin addressing this concern, I designed and co-implemented a year-long political economy action research project in South Africa's emerging Rooibos tea sector. Via participatory action research (PAR) with a team of farmer leaders and training service providers, I developed a 'Participatory Commodity Network Research' (PCNR) approach to producer-industry support. This dissertation details its conceptual framework, outlines the implementation process, and incorporates action research findings to discuss emerging Rooibos sector constraints and prospects and further problematize commodity networking potential. As I have conceptually designed the PCNR framework to ensure sociocultural flexibility, actors may adapt specific strategies to ground action analysis in diverse product sectors and regions. Complementary theories and methods frame the PCNR approach: (1) commodity network analysis, (2) sociopolitical theories of power, (3) the human capabilities approach, (4) PAR, and (5) participatory action training-of-trainers (PAToT). From this meta-framework, my project partners and I first developed a set of community workshops for initial capabilities assessment and leadership elections. Democratically elected farmer leaders then participated in multiple PAToT sessions in areas identified as most critical to market access. Training included managerial, commodity network, and research coursework and activities. As part of this process, the leaders helped develop a set of training materials and designed and facilitated workshops in their communities. In terms of research, the leaders operated as interview respondents, assisted with farmer fieldwork interviews, led final community surveys, and participated in data analysis in order to clarify the multifaceted considerations facing emerging Rooibos farmers as they seek greater representation in trade networks. The leaders also engaged with numerous industry entities and co-facilitated a commodity network policy seminar to explore opportunities for participatory information exchange (PIE) and action planning (PAP). Despite the promising efforts of many committed groups, emerging Rooibos farmers continue to operate within inequitable terrain that limits their participation and diminishes horizons. These structural impediments are mirrored throughout the value chain, with South African entities constrained by Northern conventions and control, and Northern actors impeded by overly competitive efficiency and pricing demands that hinder potential for long-term investment. Yet this dissertation also demonstrates the presence of agency throughout the Rooibos network, and it draws from the deep well of humanist knowledge to provide a set of pragmatic methods for building upon the best of this agency. If our rapidly globalizing world is to move beyond its current impasse of violent and unbridled cycles of socioeconomic growth and collapse, actors operating across the trade spectrum must transcend dichotomous and outdated assumptions in order to regain control over existing tools, knowledge, and resources and actively collaborate to more effectively realize social, economic, and environmental sustainability.
Keywords: participatory action research; political economy; Rooibos Tea; social justice; sustainability; South Africa